Exposing and overcoming the fixed-effect fallacy through crowd science. (10th February 2022) - Cyrus-Lai, Wilson; Tierney, Warren; Schweinsberg, Martin; Uhlmann, Eric Luis
Abstract: By organizing crowds of scientists to independently tackle the same research questions, we can collectively overcome the generalizability crisis. Strategies to draw inferences from a heterogeneous set of research approaches include aggregation, for instance, meta-analyzing the effect sizes obtained by different investigators, and parsing, attempting to identify theoretically meaningful moderators that explain the variability in results.